Frequency Based Substructuring Method for the Investigation of the Dynamic Behaviour of a Beam Structure / Wan Imaan Izhan Wan Iskandar Mirza ...[et al.] - Wan Iskandar Mirza, Wan Imaan Izhan; Abdul Rani, Muhamad Norhisham; Yunus, Mohd Azmi; Ahmad Basri, Ahmad Burhani; Mat Isa, Ahmad Azlan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Theoretically, the frequency based substructuring (FBS) method can be used to predict the dynamic behaviour of an assembled structure by combining some parts of the numerical and experimental frequency response functions (FRFs) of the substructures. However, the dynamic behaviour prediction via this method often leads to huge discrepancies in comparison with the test data. The discrepancies may be as a result of insufficient information on the experimental data, the rotational FRFs in particular which are very challenging to be accurately measured. One way to improve the quality of the dynamic behaviour prediction via the FBS method is by using 3D solid elements for modelling work. This is because the element type does not provide and require the rotational responses. Therefore, this study is aimed to evaluate the FRFs of a beam structure obtained from the FBS method using3D solid elements based finite element models. The test models in this study are simple aluminium beams that are coupled together using the FBS method. The resulting FRFs of the beam structure were compared with the experimental counterparts. The comparison of the FRFs showed good agreement. This indicates that there is a strong possibility of efficiently predicting the dynamic behaviour of an assembled structure using the 3D elements in FBS method.